2018
DOI: 10.1542/hpeds.2017-0215
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality After Acute Kidney Injury in the Pediatric ICU

Abstract: AKI is associated with 5- to 7-year mortality. Because this is an observational study we cannot determine if AKI is causative of mortality or of the pathophysiology. However, patients with AKI represent a high-risk group. It is reasonable that these patients be considered for targeted follow-up until future researchers better elucidate these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 37 publications
(47 reference statements)
1
39
0
1
Order By: Relevance
“…21 In noncardiac surgery children admitted to the intensive care unit, AKI has been shown to be associated with increased health care use, including postdischarge hospitalizations, physician visits, and other important health outcomes. 8,22,23 Therefore, given the known strong association of AKI with readmission and other outcomes in non-cardiac surgery populations, these findings are notable. Children undergoing cardiac surgery are at high risk of readmission, which prompts an urgent need to find easily identifiable, strong predictors that would allow for targeted interventions to reduce readmission.…”
Section: Discussionmentioning
confidence: 91%
“…21 In noncardiac surgery children admitted to the intensive care unit, AKI has been shown to be associated with increased health care use, including postdischarge hospitalizations, physician visits, and other important health outcomes. 8,22,23 Therefore, given the known strong association of AKI with readmission and other outcomes in non-cardiac surgery populations, these findings are notable. Children undergoing cardiac surgery are at high risk of readmission, which prompts an urgent need to find easily identifiable, strong predictors that would allow for targeted interventions to reduce readmission.…”
Section: Discussionmentioning
confidence: 91%
“…The longest follow-up study looked at mortality 5-7 years after hospital discharge in a non-cardiac surgery PICU population and found that AKI was associated with over 3 times higher risk of mortality (17). Interestingly, this paper demonstrated that the association between AKI and 30-day and 1-year mortality was conditional on the inclusion of hospital mortality in the outcome.…”
Section: General Picu Populationmentioning
confidence: 89%
“…Previous studies evaluating short-and long-term mortality following AKI lacked non-AKI comparison groups, however, they uniformly highlight that mortality rates in patients with AKI were higher than in the general population (12,13). Since 2015, we identified eight studies that examined the association of AKI with mortality and compared this to children who did not develop AKI, with follow-up ranging from 28-days to 5-7 years (Table 1) (3,6,(14)(15)(16)(17)(18)(19). As highlighted in Table 1, despite differences in study populations and duration of followup, all studies reported higher mortality in those with AKI when compared with children who did not experience AKI whilst in the PICU, independent of illness severity and other important confounders.…”
Section: Mortalitymentioning
confidence: 99%
“…Anak berbeda dengan dewasa, maka perhitungan dosis berdasarkan berat badan anak. Beberapa kasus CKD yang diperlukan penyesuaian dosis dengan klirens kreatinin atau laju filtrasi glomerulus [26]. Kesalahan dalam penyesuaian dosis obat dapat menyebabkan efek samping toksisitas, hasil terapi buruk, sehingga biaya pengobatan bertambah dan peningkatan lama rawat inap [27].…”
Section: Hasil Dan Diskusiunclassified